KAJIAN PERCEIVED SERVICE QUALIY TERHADAP KEPUASAN MAHASISWA UNTUK INDUSTRI JASA PERGIRUAN TINGGI SWASTA DI KOTA MALANG - Dayal Gustopo; Sanny Andjarsari; Sri Indriani (Industri Inovatif : Jurnal Teknik Industri, 2014)
Malang city has been proved as education service starting from elementary school up to higher education. This capability becomes alternative interest for Indonesian society that has an interest to continue their study in higher education. This research tries to open the gap between the service given by private university in Malang and the reality received by students who study in each university. This is important to keep the survival of private university it self and also the image of Malang city built based on the vision as TRI BINA CITRA. One of the ideas of it is to be education city that can be achieved, survived, and improved.This research is hypothesis testing that analyzed perceived service quality in university and students study service grade in each quality service dimension. Students who study in Malang University as population involved 6 private universities in Malang, consisting of 1 high education, 1 institute, and 4 universities. Proposional random sampling is used for respondent taking. and samples that are used are 401 students consist of 225 sample units from UNMUH Malang, 52 sample unit from UNMER Malang, 42 sample unit from UNISMA Malang, 10 sample unit from Machung University of Malang, 54 sample unit from ITN Malang, and 18 sample unit from STIE Malangkuceswara by criterion that respondents are in the position of fourth semester and up when pre test questioner is tried in October 2009.The research shows there is a negative gap for all service quality dimensions with the biggest negative score in empathy dimension and reliability dimension. Service quality proved that students service study influenced by. The research finding shows that the service quality in private university is influenced by service quality by reliability, responsiveness, empathy, and tangible dimension.